Umm an-Nar Ritual Building in Dahwa 1 (DH1), Northern Al-Batinah, Oman - Ğawharī, Nāṣir Saʻīd ʻAlī al- (Near Eastern archaeology, 2021)
The Umm an-Nar Culture was identified after the first scientific archaeological excavations took place in the Oman Peninsula (modern-day Oman and United Arab Emirates) during the late 1950s by the Danish team at the Umm an-Nar Island in Abu-Dhabi (Frifelt 1991, 1995). Since then, several sites have been excavated by different teams in the region, such as Hili (Cleuziou 1980, 1982), Ras al-Jinz (Cleuziou and Tosi 2000), Bat (Thornton, Cable, and Possehl 2016), Meyaser (Weisgerber 1978, 1981), Bisya/Salut (Orchard and Stanger 1999; Orchard and Orchard 2002), Tell Abraq (Potts 1989, 1990, 1991, 2000), and Asimah (Vogt 1994). These excavations have revealed abundant material about the culture of these third-millennium BCE (2700-2000 BCE) communities. The inhabitants of this region had developed an intensive and complex long-distance trade network with societies in Mesopotamia and the Indus Valley (Cleuziou 2003).